FOOD CONSUMPTION PATTERNS IN TODDLERS IN LOKUS STUNTING VILLAGE, BUNGO DISTRICT - Perdana, Silvia Mawarti; M. Ridwan (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2023)
background:The Indonesian Nutrition Status Study (SSGI) in 2021 showed that Bungo Regency data has a stunted toddler prevalence of 22.9%. Several research results have shown that the problem of stunting in toddlers is related to low protein intake in daily food consumption. On the other hand, Jambi Province has local food sources of protein, especially freshwater fish as an alternative to daily side dishes. This study aims to examine the pattern of protein food consumption in Sungai Mengkuang and Sungai Puri Village as Bungo Regency's stunting locus village. Method: Quantitative methods are used to measure the toddler's pattern of protein food consumption with a food frequency questionnaire and food recall. Result: The results showed that food protein consumption was already contained in children's complementary feeding, but with the number of servings that did not meet the balanced nutrition guidelines (< 100% daily recommendations). Discussion: As many as 63.5% of respondents have received complementary feeding â‰¥ three times a day. Conclusion: It is necessary to optimize the production, distribution, and consumption of local protein foods as a solution to accelerate reduction of stunting.